Unhappy Development : Dissatisfaction with Life on the Eve of the Arab Spring - Arampatzi, Efstratia; Burger, Martijn; Ianchovichina, Elena; Röhricht, Tina; Veenhoven, Ruut (World Bank, Washington, DC, 2015)
Despite progress in economic and social development in the 2000s, there was an increasing dissatisfaction with life among the population of many developing Arab countries. At the end of the decade, these countries ranked among the least happy economies in the world—a situation that fits the so-called “unhappy development” paradox. The paradox is defined as declining levels of happiness at a time of moderate-to-rapid economic development. This paper empirically tests the strength of association of a range of objective and subjective factors with life evaluation in the Middle East and North Africa region in the years immediately preceding the Arab Spring uprisings (2009–10). The findings suggest a significant, negative association between life satisfaction levels in the region during this period and each of the main perceived reasons for the 2011 uprisings—dissatisfaction with the standard of living, poor labor market conditions, and corruption.